2009
DOI: 10.1038/nchembio.179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the toxic trigger in mushroom poisoning

Abstract: We have isolated the small, highly strained carboxylic acid cycloprop-2-ene carboxylic acid from the Asian toxic mushroom Russula subnigricans. This compound is responsible for fatal rhabdomyolysis, a new type of mushroom poisoning that is indicated by an increase in serum creatine phosphokinase activity in mice. We found that polymerization of the compound at high concentrations via ene reaction abolishes its toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 16 publications
2
58
0
1
Order By: Relevance
“…Patients may recover or may present with delayed complaints of muscle pain and weakness, with associated rhabdomyolysis, myoglobinuria, renal failure, and hyperkalemia. Speech impairment, convulsions, and loss of consciousness have also been reported [143,144].…”
Section: Clinical Presentationmentioning
confidence: 95%
See 2 more Smart Citations
“…Patients may recover or may present with delayed complaints of muscle pain and weakness, with associated rhabdomyolysis, myoglobinuria, renal failure, and hyperkalemia. Speech impairment, convulsions, and loss of consciousness have also been reported [143,144].…”
Section: Clinical Presentationmentioning
confidence: 95%
“…subnigricans contains cycloprop-2-ene carboxylic acid, which triggers rhabdomyolysis [143]. In Asia, ingestion of R. subnigricans typically results in nausea, vomiting, and diarrhea within 30 min to 2 h of ingestion.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apsinuodijimas nuodingąja ūmėde ir žalsvuoju baltiku (Tricholoma equestre) gali sukelti rabdomiolizę, ūminį inkstų nepakankamumą, sunkų elektrolitų disbalansą (hiperkalemiją, hipokalcemiją), kvėpavimo sistemos nepkankamumą, plaučių edemą, skilvelinę tachikardiją ir kardiovaskulinį šoką [1,5,6,29,32]. Kai kuriais atvejais rabdomiolizė pažeidžia ne tik inkstus ir sutrigdo elektrolitų balansą, bet ir sukelia miokarditą, aritmijas, kardiovaskulinį kolapsą ir baigiasi mirtimi [29].…”
Section: Rabdomiolizės Sindromasunclassified
“…Furthermore, 5 was stable in aqueous solutions containing L-cysteine, both at room temperature and after heating at 60°C (Figure S3), in agreement with previous studies on related methylcyclopropenes. [19] Interestingly, when heated to 60°C in the presence of Lcysteine, we found that trans-cyclooctenol [rel-(1R,4E,pR)-cyclooct-4-enol] isomerized slowly to cis-cyclooctenol ( Figure S4). Although further work will be needed to determine the relevance of this phenomenon for bioconjugation, it does illustrate that, under certain conditions, methylcyclopropenes may possess superior stability to trans-cyclooctenes, because cyclopropenes are not subject to this cis/trans isomerization.…”
mentioning
confidence: 99%